Agility as a Strategic Enabler: Unpacking the Digital Transformation–Performance Nexus in Healthcare - Zulfikri, Agung (Indonesian Scientific Publication, 2025)
Healthcare organizations are undergoing rapid digital transformation (DT), incorporating technologies such as AI, IoT, and telemedicine. However, technological adoption alone does not guarantee improved outcomes. This study investigates the mediating role of organizational agility in the relationship between DT and competitive advantage, aiming to understand how agility enables healthcare institutions to realize the full potential of digital investments. A cross-sectional quantitative design was employed, surveying 250 healthcare professionals from public and private hospitals. Constructs included digital transformation (measured by technology adoption), organizational agility (responsiveness, adaptability), and competitive performance (efficiency, innovation, satisfaction). Data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with bootstrapping (n = 5000) used to test mediation effects. The results revealed that private hospitals reported higher DT scores (72.3) than public hospitals (56.5). Organizational agility emerged as a significant mediator in the DT–performance relationship. Path coefficients confirmed: DT → Agility (β = 0.61, p < 0.001) Agility → Competitive Advantage (β = 0.68, p < 0.001) DT → Competitive Advantage (Direct: β = 0.29, Indirect via Agility: β = 0.41). Agility was found to enhance responsiveness, enable real-time adaptation, and foster innovation. Organizations with higher agility demonstrated superior operational efficiency and patient satisfaction. The findings align with dynamic capabilities theory, which positions agility as essential for navigating digital disruption. Organizational agility is a foundational capability for translating digital transformation into strategic advantage in healthcare. Leaders must invest in agile structures, training, and culture to fully leverage digital tools. This study contributes to the literature by empirically validating agility’s role in digital healthcare strategy and offers a framework for future implementation and evaluation.